Issues of Arabic Poetic Theory - Youcef, Baghdad (Journal of Ecohumanism, 2025)
This research paper aims to reinterpret the concepts of Arabic poetic theory by examining the definition of poetics and its transition into Arabic criticism, as well as the concept and value of poetry among the Arabs, and discussing the main issues of Arabic poetry addressed by classical criticism. One of the most important findings that can be reached through revisiting the Arab critical heritage on poetry is that the Arab understanding of poetry differs from that of others, based on the distinct characteristics of Arabic poetry. Moreover, Arabic criticism can arrive at identifying general rules and foundations that help establish the features of a coherent epistemological theory of poetry one that is comprehensive and built on philosophical and logical perspectives comparable to practical Western theories.